Reflective Village Leadership and Everyday Politics: An Autoethnographic Study from Labanan Makmur, Indonesia (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Village leadership in Indonesia is often portrayed in technocratic and administrative terms, focusing on budget allocation, program delivery, and regulatory compliance. Such perspectives overlook the relational, cultural, and political dimensions of governance as lived in everyday community life. This paper explores reflective village leadership in Labanan Makmur, East Kalimantan, through an autoethnographic approach, drawing on the author’s six-year experience as village head (2017–2023). Data were derived from field diaries, village documents, participant observation, and informal dialogues with community members. Analysis was conducted thematically, guided by Foucault’s notion of power/knowledge, Scott’s concept of everyday politics, Freire’s idea of emancipatory participation, Parsons’ AGIL framework, and theories of social capital (Putnam, Bourdieu). Findings reveal four interrelated dynamics. First, power in village governance is a circulating practice, negotiated across formal institutions and informal arenas such as coffee stalls and WhatsApp groups. Second, reflective leadership engages with everyday politics, treating gossip, rumors, and community debates as integral feedback loops. Third, participation emerges as an emancipatory practice, where villagers co-create decisions through dialogue, collective agency, and symbolic action. Finally, innovation grows from social capital, with women’s savings groups, youth initiatives, and collective labor networks becoming institutionalized as grassroots innovations. The study argues that reflective leadership transforms governance from bureaucratic routine into a participatory and emancipatory practice, grounded in trust, reciprocity, and cultural legitimacy. It contributes to broader debates on rural governance by showing how leaders who embrace reflexivity and everyday politics can build more inclusive and resilient community institutions.